Substrate utilization during submaximal exercise in children with a severely obese parent - Eaves, Audrey D.; Colon, Ashley; DuBose, Katrina D.; Collier, David N.; Houmard, Joseph A. (My University, 2012)
Background We have reported a reduction in fatty acid oxidation (FAO) at the whole-body level and in skeletal muscle in severely obese (BMI ≥ 40 kg/m2) individuals; this defect is retained in cell culture suggesting an inherent component. The purpose of the current study was to determine if an impairment in whole-body fatty acid oxidation (FAO) was also evident in children with a severely obese parent. Methods Substrate utilization during submaximal exercise (cycle ergometer) was determined in children ages 8–12 y with a severely obese parent (OP, n = 13) or two lean/non-obese (BMI range of 18 to 28 kg/m2) parents (LP, n = 13). A subgroup of subjects (n = 3/group) performed 4 weeks of exercise training with substrate utilization measured after the intervention. Results The children did not differ in age (LP vs. OP, respectively) (10.7 ± 0.5 vs. 10.2 ± 0.5 y), BMI percentile (65.3 ± 5.2 vs. 75.9 ± 7), Tanner Stage (1.4 ± 0.2 vs. 1.5 ± 0.2), VO2peak (40.3 ± 2.7 vs. 35.6 ± 2.6 ml/kg/min) or physical activity levels (accelerometer). At the same absolute workload of 15 W (~38% VO2peak), RER was significantly (P ≤ 0.05) lower in LP vs. OP (0.83 ± 0.02 vs. 0.87 ± 0.01) which was reflected in a reduced reliance on FAO for energy production in the OP group (58.6 ± 5.1 vs. 43.1 ± 4.0% of energy needs during exercise from FAO). At a higher exercise intensity (~65% VO2peak) there were no differences in substrate utilization between LP and OP. After exercise training RER tended to decrease (P = 0.06) at the 15 W workload, suggesting an increased reliance on FAO regardless of group. Conclusions These findings suggest that the decrement in FAO with severe obesity has an inherent component that may be overcome with exercise training.
Keywords: Bariatric surgery, Class III obesity, Exercise, Fat oxidation, Skeletal muscle